Cyclical component impact on high-technology export dynamics in Poland - Belov, Aleksandr (Herald of Economics, 2023)
Introduction. This article is part of a general study of the numerical assessment of the country’s scientific and technical development impact on its economic growth. It is included in its first part, which considers the analysis of the production and the export of high-tech products dynamics in different world countries. This will give Ukraine the opportunity to use certain positive experiences and take into account negative trends in the process of restoring its own economy in the post-war period.Purpose. The purpose is to determine the degree of cyclical component impact on the export of high-tech products dynamics in Poland.Methods. As a tool of state regulation in the field of innovation and scientific and technical development, the author’s methodology for analyzing the structure of the high- tech products export dynamics was proposed. The methodology reveals the economic meaning and allows to distinguish the following components in the structure of the high- tech products export dynamics: uniform growth; accelerated growth; cyclical growth. And it also allows us to consider how the share of the cyclical component impact changes, if high-tech exports are considered as a share of all industrial exports and as a share of GDP, and also compared with the structure of the country’s GDP dynamics as a whole.Conclusions. The research showed that the Poland high-tech export dynamics has a cyclical nature of development. Economic cycles with periods of 9.3 and 9.6 years were determined and the level of influence of the cyclical component on the general trend was calculated, which is 1.5 and 2 times slower relative to the similar dynamics of countries such as Austria and Germany. The determined overall weighted impact of the cyclical component on the high-tech exports dynamics is quite significant and ranges from -8.19% to 19.15%.Discussion. The obtained study results will ensure the implementation of an effective state policy for the Ukraine economy recovery in the post-war period.